2019
DOI: 10.25165/j.ijabe.20191201.3270
|View full text |Cite
|
Sign up to set email alerts
|

Energy balance and environmental impacts of rice and wheat production: A case study in Nepal

Abstract: Energy and environment are the key concerns in todays' agriculture. This study investigated energy balance and environmental impact of rice and wheat production systems in terms of energy ratio, impact of energy inputs to the crop yield and CO 2 e (carbon dioxide equivalent) emissions under terai and hill geographical regions of Nepal. Primary data were collected from 139 randomly selected farms by using structured questionnaire. The results revealed that the total energy consumption in rice and wheat producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Among all livestock products, particularly the production of mutton/pork/bovine meat F I G U R E 3 Environmental variables assessed in the included studies. [16][17][18][19][20][21][22][23][24][25][27][28][29][30][31][32][33][35][36][37][38][39][40][41][43][44][45]56 had the highest GHG emissions. 16,17,19,21,22 In a few studies where the authors considered dairy products along with eggs and meat in the category of livestock, based on the consumption pattern of Indians, dairy products or eggs contributed a greater percentage of GHG emissions compared to meat.…”
Section: Indiamentioning
confidence: 99%
See 2 more Smart Citations
“…Among all livestock products, particularly the production of mutton/pork/bovine meat F I G U R E 3 Environmental variables assessed in the included studies. [16][17][18][19][20][21][22][23][24][25][27][28][29][30][31][32][33][35][36][37][38][39][40][41][43][44][45]56 had the highest GHG emissions. 16,17,19,21,22 In a few studies where the authors considered dairy products along with eggs and meat in the category of livestock, based on the consumption pattern of Indians, dairy products or eggs contributed a greater percentage of GHG emissions compared to meat.…”
Section: Indiamentioning
confidence: 99%
“…With almost 66% of people earning their livelihood in the agriculture sector, Nepal can be deemed as an agriculture-based country. In our review, all five studies [36][37][38][39][40] identified from Nepal focused on GHG emissions. Two studies 38,39 conducted by Pokhrel and Soni 38,39 utilised primary data collected from farmers (information about inputs such as seeds, labour, draft animal, farmyard manure, chemical fertilisers, diesel fuel, farm machinery and farm tools).…”
Section: Nepalmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few such studies, however, have been conducted in Nepal. A comparative study of energy and environment impact analysis was conducted by Pokharel and Soni in 2019 (Pokhrel and Soni 2019) for two crops (rice and wheat) via a survey of two western districts: Banke for terai land and Surkhet for hilly terrain within Nepal. The study has concluded that the rice production via terai land and wheat production in a hilly region are more energy and environmentally efficient.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial differences in the value of individual ecosystem services in the energy subsystem are due to population density, heavy industry development, and transportation lines. Grain production peaks in the belly of the study area because of more suitable land cover type, slope, water availability, and environmental factors compared to the highlands(Boisvert et al 2013;Pokhrel and Soni 2019). Furthermore, urban expansion and water storage reduce the quality of cultivated land, resulting in fragmentation, low grain production capacity, and spatial differences in the value of individual ecosystem services in the food subsystem.The interaction of WEF based on GEPBoth the trade-off and the synergy of the value of the ecosystem service function are of utmost importance to the management of the ecosystem and the sustainable development of the region.…”
mentioning
confidence: 99%